A Family Affair: A Quantitative Analysis of Third-Generation Successors’ Intentions to Continue the Family Business - Chan, Francine; Jalandoni, Dominique; Sayarot, Cecil Austin; Uy, Marc; Daradar, Denver; Aure, Patrick (Organizations and Markets in Emerging Economies, 2020)
Family businesses face a succession crisis where only 13% survive until the third generation (Lee-Chua, 2014). While there is sufficient literature on family business succession planning , research on the motivations behind next-generation engagement in family firms, especially for third-generation successors, is limited (Garcia, Sharma, De Massis, Wright & Scholes, 2018). Thus, the present study tested Garcia et al. (2018)’s model where perceived parental support and psychological control predict next-generation engagement, with family business self-efficacy and commitment to family business mediating this relationship. 118 third-generation successors were surveyed using established and newly developed scales based on previous literature. Mediation analysis showed that normative commitment partially mediated verbal encouragement and next-generation engagement, while affective commitment fully mediated parental psychological control and next-generation engagement. Results were also compared against 124 second-generation successors, revealing that there were no significant differences between generations. Combining these two datasets led to a new conceptual framework, where normative commitment partially mediated verbal encouragement and next-generation intention, while affective commitment partially mediated parental psychological control and next-generation intention. The results of the study can contribute to the enrichment of family business literature, particularly on the factors that influence the intentions of third-generation successors, and to the creation of effective succession plans.